2012
DOI: 10.1063/1.4735002
|View full text |Cite
|
Sign up to set email alerts
|

Long minority carrier lifetime in Au-catalyzed GaAs/AlxGa1−xAs core-shell nanowires

Abstract: Charge recombination in disordered neat polymer films under imbalanced excitation conditions studied using the recombination time of flight technique J. Appl. Phys. 111, 104510 (2012) Dual roles of doping and trapping of semiconductor defect levels and their ramification to thin film photovoltaics J. Appl. Phys. 111, 104509 (2012) Ultrafast carrier response of Br+-irradiated In0.53Ga0.47As excited at telecommunication wavelengths J. Appl. Phys. 111, 093721 (2012) Electron traps in amorphous In-Ga-Zn-O thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
97
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 25 publications
6
97
1
Order By: Relevance
“…It has been shown that the optimum temperature for Al1-yGayAs layer is 750 °C. 46,47 The strongest PL emission intensity for the GaAs1-xSbx QW nanowires occurs at 725 °C. The PL spectrum shift with growth temperature does not show a clear trend, as both blue and red shifts are observed (see Figure 2a).…”
Section: Optical Properties Of the Qw Nanowires: High Iqementioning
confidence: 99%
“…It has been shown that the optimum temperature for Al1-yGayAs layer is 750 °C. 46,47 The strongest PL emission intensity for the GaAs1-xSbx QW nanowires occurs at 725 °C. The PL spectrum shift with growth temperature does not show a clear trend, as both blue and red shifts are observed (see Figure 2a).…”
Section: Optical Properties Of the Qw Nanowires: High Iqementioning
confidence: 99%
“…6 Several crucial steps have been taken toward the realization of high-mobility devices based on this new class of nano-materials and their integration. 7 Single-crystal, defect-free cores using several III-V's, 8,9 selective radial doping, 10 high quality interfaces, 11 and integration with Si substrates 12 have been realized. Figure 1 show the schematics of a prototypical GaAs/AlGaAs radial heterojunction.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical identity of the involved defects was extensively studied for planar GaNP [18][19][20] where the non-radiative recombination was shown to originate from point defects formed in bulk regions of the alloy. In the case of NWs, however, increasing surface-to-volume ratio raises importance of recombination processes via surface states [17,21,22], however, the origin of these states is so far poorly understood. Existing reports on defect formation in III-V NWs and associated core/shell nanostructures were primarily focused on extended defects [23][24][25][26], which seem to be of limited importance in carrier recombination.…”
mentioning
confidence: 99%